2022
DOI: 10.3389/fspor.2021.798941
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Heart Rate Monitoring on Ratings of Perceived Exertion and Attention Allocation in Individuals of Varying Fitness Levels

Abstract: There has been a rapid increase in the use of wearable technology-based physical activity trackers. Most of these physical activity trackers include tracking and displaying the individual's heart rate (HR). There is little known about how HR monitoring influences the perception of exertion and attention allocation. Shifting attentional focus toward the body (association), such as monitoring HR, instead of environmental stimuli (dissociation) may increase one's perceived level of exertion. The purpose of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Furthermore, RPE corresponds to the HR range of a healthy young male (60-−200 beats/min) and HR can be predicted by multiply the RPE value by 10. Recently, Braun-Trocchio et al ( 8 ) found that participants' HR and RPE both increased linearly with time and effort during a stepping task. This finding demonstrates that estimations of an individual's RPE can be reliably obtained using HR values.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, RPE corresponds to the HR range of a healthy young male (60-−200 beats/min) and HR can be predicted by multiply the RPE value by 10. Recently, Braun-Trocchio et al ( 8 ) found that participants' HR and RPE both increased linearly with time and effort during a stepping task. This finding demonstrates that estimations of an individual's RPE can be reliably obtained using HR values.…”
Section: Introductionmentioning
confidence: 99%
“…Also, sleep quality could be a confounding variable that may influence the relationship between examined variables [48] but which could not be evaluated here. Likewise, a direct measure of heart rate response during the 20 m incremental shuttle run test (Course Navette test) could be a relevant indicator of an individual's physical fitness level [49]. Both should be considered in future studies.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…Wearable smartwatches and fitness trackers have tremendously grown in commercial popularity within the last two decades (Braun-Trocchio et al, 2022). It is no secret that wearable technology companies continually add and utilize more sensors in their devices (Ringuet-Riot et al, 2013).…”
Section: Introductionmentioning
confidence: 99%